Product green degree, service free-riding, strategic price difference in a dual-channel supply chain based on dynamic game. (4th March 2022) - Liang, Yu; Sun, Xiaochen
Abstract : In this paper, we study a green product dual-channel supply chain with a manufacturer and a retailer. The service free-riding is considered, and the channel price difference is also introduced as a strategic tool to adjust the channel conflict. In centralized and decentralized models, we give the optimal decisions of the supply chain members and analyse the effects of the service free-riding and the price difference on the related decisions. In order to coordinate the dual-channel green supply chain, we also design a two-part tariff contract coordination model, which allows both the manufacturer and the retailer to obtain a win–win result. From the analytical and numerical results, we find that the proper service free-riding degree and price difference are beneficial to the decision makers and the greening of supply chain. And in the centralized model, when the degree of service free-riding is small, the increase of the channel price difference can stimulate the manufacturer to provide the lower price product with lower service and green degree, otherwise, it is the opposite. Besides, the result also shows that, except for consumers, the centralized model always performs better than the decentralized model in the profit and social welfare aspects.